Strategies For Increasing Employee Performance During The Covid-19 Pandemic At The Special Mom And Child Hospital (RSKIA) ANNISA In Banjarmasin - Suhartina saleng; M. Riduansyah Syafari; Ahmad Yunani (International Journal of Politic, Public Policy and Environmental Issues, 2021)
Banjarmasin City in 2020 became the area with the most COVID-19 distribution in South Kalimantan. Under these conditions, RSKIA Annisa Banjarmasin is required to continue to work professionally in providing health services. The COVID-19 pandemic has limited service activities and become an obstacle, thus disrupting the optimization of employee performance. In this context, an appropriate employee performance improvement strategy is needed, to develop employee performance, namely in addition to achieving organizational goals, employee performance remains optimal, employee safety is also maintained. Therefore, during the COVID-19 pandemic, it is important to review strategies for improving employee performance during COVID-19 pandemic. The results of the study describe that the strategy for improving employee performance at RSKIA Annisa Banjarmasin City during the Covid-19 Pandemic was carried out through program steps aimed at maintaining the stability of employee performance during difficult and uncertain conditions. The steps taken include giving awards for performance that has been carried out during the Covid-19 Pandemic. This is intended to provide a motivational boost to performance to produce better work.